Use of Informatics Textbooks in School Classroom - Hajdin, Goran; Divjak, Blaženka (Journal of Information and Organizational Sciences, 2016)
Textbooks are an integral part of school classroom teaching. Their use has been researched for the past few decades with a focus on a wide variety of aspects. This paper is focused on the published literature relative to textbooks with a special focus on the pedagogical use of textbooks within school classroom of informatics. Sixty two papers of various topics related to textbooks have been analyzed. The focus was placed on a) identifying the most influential papers related to textbooks where we identified nine key papers; b) prevailing topics in research papers related to informatics’ textbooks where analysis showed that most papers related to textbooks and informatics are focused on textbook content; c) identifying which topics have been researched in other fields related to use of textbooks but have not been so far included in surveys related to informatics subject, where we identified five main categories of topics researched in other fields.